Youth empowerment and contraceptive use in Nepal - Shrestha, Bidhya (Nepal Population Journal, 2018)
Contraceptive choices have an enormous impact on health, schooling and employment prospects. Access to full range of contraceptive method is vital for ensuring the health of youth. This study examined the association between youth empowerment in the domestic sphere and contraceptive use among currently married female youth in Nepal using the data of Nepal Demographic Health Survey, 2011. A sample of 2,553 currently married women of reproductive age 15-24 were chosen for this study. Bivariate analysis with cross tabulation and chi-square test were used to examine the association between each independent and dependent variables. Logistic regression model was employed for examining the effect of each independent variable as well as control variable on dependent variable. Result showed that the effect of youth empowerment remains statistically significant and has influence on their use of contraceptives, even after adding the control variables into the model. Youth who are empowered they use contraceptive about 2 times higher than those who are not empowered. Influence of some selected socio-economic and demographic variables on contraceptive are also examined. The study shows that the presence of son at home on contraceptive use is strongly associated (OR=4.58). Thus youth empowerment is necessary to increase contraceptive use.